Detoxification Toxin Carcinogenic and Non Carcinogenic - Syamsiar S Russeng, Abdul Rohim Tualeka, Ng Yee Guan,; Ahsan, Ahsan; Susilowati, Indri H; Rahmawati, Pudji; Nurmianto, Eko; Firdaus, Muhamad; Ain, Khusnul (Opción, 1970)
The purpose of this analysis is to determine the detoxification of cancer-causing and non-cancerous toxins. A comprehensive literature search was conducted to identify, biotransformation and detoxify toxins as well as various supporting studies. Original research articles published in English academic journals were obtained through literature searches with electronic databases such as Scopus, ScienceDirect, PubMed and Google Scholar. Various sources and studies state that detoxification of toxins can be carried out using food. Foods that can detoxify toxins are enzyme-rich foods in stage two biotransformation such as foods containing the enzymes CYP2E1, glutathione and sulfation.